Diagnosis of Pfeiffer Syndrome with Umbilical Hernia - Bhesham Kumar Shahani; Aneel Kumar Vaswani; Waseem Mehmood Nizamani (ziauddin University, 2024)
Pfeiffer syndrome (PS) is a form of acrocephalosyndactyly, a group of rare genetic syndromes, and is characterized by variable degrees of bicoronal craniosynostosis, variable hand and foot malformations and various other associated manifestations. Type I Pfeiffer syndrome is compatible with life. It is characterized by normal intelligence and a classic phenotype of craniosynostosis, broad thumbs, and syndactyly. Types II and III are sporadic in occurrence, with more severe involvement of the central nervous system (CNS) than in type I. Type II is associated with the classic cloverleaf-shaped skull. Neurologic compromise is common in both types II and III. Key Words: Autoimmune Pfeiffer Syndrome (PS), Acrocephalosyndactyly, Craniosynostosis.